2017
DOI: 10.1007/s40120-017-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta and Tau as Alzheimer’s Disease Blood Biomarkers: Promise From New Technologies

Abstract: The utility of the levels of amyloid beta (Aβ) peptide and tau in blood for diagnosis, drug development, and assessment of clinical trials for Alzheimer’s disease (AD) has not been established. The lack of availability of ultra-sensitive assays is one critical issue that has impeded progress. The levels of Aβ species and tau in plasma and serum are much lower than levels in cerebrospinal fluid. Furthermore, plasma or serum contain high levels of assay-interfering factors, resulting in difficulties in the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 78 publications
1
55
0
Order By: Relevance
“…immunoaffinity‐based assays) now available in the market such as immunomagnetic reduction (IMR) and single molecule array (SIMOA) must be considered in future studies to overcome the challenges of detection encountered using ELISA‐based technique. Both IMR and SIMOA, although promising, still need validation in different populations by means of multicentre studies (Lue, Guerra, & Walker, ). Lastly, readers should interpret the present results with caution.…”
Section: Discussionmentioning
confidence: 99%
“…immunoaffinity‐based assays) now available in the market such as immunomagnetic reduction (IMR) and single molecule array (SIMOA) must be considered in future studies to overcome the challenges of detection encountered using ELISA‐based technique. Both IMR and SIMOA, although promising, still need validation in different populations by means of multicentre studies (Lue, Guerra, & Walker, ). Lastly, readers should interpret the present results with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, much effort has been devoted to global research and as a result several blood-based biomarkers have been developed [19,20]. These blood-based biomarkers have demonstrated high correlation between the level of Aβ42, Aβ40, and the risk of AD [21,22], but they require highly sensitive equipment to detect low-concentrated target proteins. On the other hand, MDS-OAβ utilizes spiking of purified synthetic Aβ into plasma and incubation thereafter to measure the level of AβO tendencies in plasma [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new ultrasensitive technologies with superior sensitivity and specificity for measuring blood-base biomarkers, such as an immunomagnetic reduction (IMR) assay, single molecule array (SIMOA), immunocapture-based multiplexing systems (xMAP) immunoprecipitation-mass spectrometry (IP-MS), and modified sandwich ELISA, have been developed [9][10][11][12]. Clinical studies using these technologies reported that significant changes in concentrations of plasma Aβ 1-42 and the ratio of plasma Aβ 1-42 /Aβ 1-40 are associated with risk of AD [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%